Enter a problem...
Algebra Examples
9(x-9)=-119(x−9)=−11
Step 1
Step 1.1
Divide each term in 9(x-9)=-119(x−9)=−11 by 99.
9(x-9)9=-1199(x−9)9=−119
Step 1.2
Simplify the left side.
Step 1.2.1
Cancel the common factor of 99.
Step 1.2.1.1
Cancel the common factor.
9(x-9)9=-119
Step 1.2.1.2
Divide x-9 by 1.
x-9=-119
x-9=-119
x-9=-119
Step 1.3
Simplify the right side.
Step 1.3.1
Move the negative in front of the fraction.
x-9=-119
x-9=-119
x-9=-119
Step 2
Step 2.1
Add 9 to both sides of the equation.
x=-119+9
Step 2.2
To write 9 as a fraction with a common denominator, multiply by 99.
x=-119+9⋅99
Step 2.3
Combine 9 and 99.
x=-119+9⋅99
Step 2.4
Combine the numerators over the common denominator.
x=-11+9⋅99
Step 2.5
Simplify the numerator.
Step 2.5.1
Multiply 9 by 9.
x=-11+819
Step 2.5.2
Add -11 and 81.
x=709
x=709
x=709
Step 3
The result can be shown in multiple forms.
Exact Form:
x=709
Decimal Form:
x=7.‾7
Mixed Number Form:
x=779